Noble Gases in Interplanetary Dust Particles, II: Excess Helium-3 in Cluster Particles and Modeling Constraints on Interplanetary Dust Particle Exposures to Cosmic-Ray Irradiation - Pepin, Robert O.; Palma, Russel L.; Schlutter, Dennis J. (Meteoritics & Planetary Science, 2001)
Measurements of He isotopes in cluster interplanetary dust particles (IDPs) from stratospheric dust collector L2009 reveal anomalous 3He/4He ratios comparable to those seen earlier, up to ∼40x the solar wind ratio, in particles from the companion collector L2011. These overabundances of 3He in the L2009 samples are masked by much higher 4He contents compared to the L2011 particles, and are visible only in minor gas fractions evolved by stepwise heating at high temperatures. Cosmic-ray induced spallogenic reactions are efficient producers of 3He. The majority of this paper is devoted to a detailed assessment of the possible role of spallation in generating the 3He excesses in these and other cluster IDPs. A model of collisional erosion and fragmentation during inward transit through the interplanetary dust environment is used to estimate space lifetimes of particles from asteroidal and Edgeworth–Kuiper Belt sources. Results of the modeling indicate that Poynting–Robertson orbital evolution timescales of IDPs small enough to elude destruction on their way to Earth from either location are far shorter than the cosmic-ray exposure ages required to account for observed 3He overabundances. Grains large enough to have sufficiently long space residence times are fragmented close to their sources. An alternative to long in-space exposure could be prolonged irradiation of particles buried in parent body regoliths prior to their ejection as IDPs. A qualitative calculation suggests, however, that collisional erosion of asteroidal upper-regolith materials is likely to occur on timescales shorter than the > 1 Ga burial times needed for accumulation of spallogenic 3He to the levels seen in several cluster particles. In contrast, regoliths on Edgeworth–Kuiper Belt objects may be stable enough to account for the 3He excesses, and delivery of heavily pre-irradiated IDPs to the inner solar system by short-period Edgeworth–Kuiper Belt comets remains a possibility. A potential problem is that the expected associated abundances of spallation-produced 21Ne appear to be absent, although here the present IDP data base is too sparse and for the most part too imprecise to rule out a spallogenic origin. Relatively short periods of pre-ejection residence in asteroidal regoliths may be responsible for the curiously broad exposure age distributions reported for micrometeorites extracted from Greenland and sea-floor sediments.